The heritability of reading and reading-related neurocognitive components: A multi-level meta-analysis. (February 2021) - Andreola, Chiara; Mascheretti, Sara; Belotti, Raffaella; Ogliari, Anna; Marino, Cecilia; Battaglia, Marco; Scaini, Simona
Highlights: Heritability estimates vary widely across reading-related neurocognitive skills. Age- and school grade-specific genetic influences have been reported. Previous meta-analyses focused on some reading skills without controlling for moderators. Reading-related skills show moderate-to-substantial meta-heritability estimates. School grade levels moderated the heritability of some reading-related skills. Abstract: Reading ability is a complex task requiring the integration of multiple cognitive and perceptual systems supporting language, visual and orthographic processes, working memory, attention, motor movements, and higher-level comprehension and cognition. Estimates of genetic and environmental influences for some of these reading-related neurocognitive components vary across reports. By using a multi-level meta-analysis approach, we synthesized the results of behavioral genetic research on reading-related neurocognitive components (i.e. general reading, letter-word knowledge, phonological decoding, reading comprehension, spelling, phonological awareness, rapid automatized naming, and language) of 49 twin studies spanning 4.1–18.5 years of age, with a total sample size of more than 38, 000 individuals. Except for language for which shared environment seems to play a more important role, the causal architecture across most of the reading-related neurocognitive components can be represented by the following equation a² > e² > c². Moderators analysis revealed that sex and spoken language did not affect the heritability of any reading-related skills; school grade levels moderated the heritability of general reading, reading comprehension and phonological awareness.